2018
DOI: 10.1016/j.fuel.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effect of orifices inclination angle in multihole diesel injector nozzles. Part 1 – Hydraulic performance

Abstract: Nozzle hydraulic performance has a significant impact on diesel spray development and combustion characteristics. Thus, it is important to understand the links between the nozzle geometry, the internal flow features and the spray formation. In this paper, a detailed analysis of the impact of the nozzle orifices inclination angle on its hydraulic performance is performed. For this purpose, three different nozzles with included angles of 90, 140 and 155 degrees are evaluated. Instantaneous injection rate and mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…to 200 MPa (the same ones already seen for the hydraulic tests presented in [46]) at an ambient density of 50 kg/m 3 . The energizing time for these tests has been fixed at 1.5 ms for all the cases.…”
Section: Uthsupporting
confidence: 78%
See 3 more Smart Citations
“…to 200 MPa (the same ones already seen for the hydraulic tests presented in [46]) at an ambient density of 50 kg/m 3 . The energizing time for these tests has been fixed at 1.5 ms for all the cases.…”
Section: Uthsupporting
confidence: 78%
“…Regarding the other two nozzles, spray penetration is very similar for both of them, although the trend of reducing spray penetration when increasing the included angle is still appreciable. The relatively low differences between the nozzles is likely due to the effect of the inclination angle on the inlet rounding radii produced during the hydrogrinding process, as already discussed in [46]. The maximum spray penetration observed in the images is related to the arrival of the spray tip to the end of the visualization window.…”
Section: Spray Penetration Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…A review of the literature revealed that test fluids for most studies were air, diesel fuel, water and glycerol (for high viscosity which is still relatively low) and focus was on angle orientations, entrance shape, cavitation number, design of nozzle; and for more recent studies, number of holes on the nozzletermed multi-hole nozzles (Zhong et al, 2014;Sun et al, 2015;Desantes et al, 2016;Zhou et al, 2016;Salvador et al, 2017). Some studies considered the length and diameter of the nozzles as separate factors.…”
Section: Introductionmentioning
confidence: 99%